2020
DOI: 10.1186/s12889-020-09095-5
|View full text |Cite
|
Sign up to set email alerts
|

The impact of sleep deprivation and alcohol on driving: a comparative study

Abstract: Background: There is concern about the detrimental effects of shift-workers' increasing working hours particularly when driving sleep deprived. The approach to measuring the magnitude of driving impairment caused by sleep deprivation was by comparing it to alcohol. The study compared driving performance after 24-h of wakefulness to performance with a BrAC of just over 22 μg/100mls of breath which is equal to 50 mg of alcohol per 100mls of blood (Scottish drink-drive limit). The effectiveness of coffee as a cou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 55 publications
(69 reference statements)
1
7
0
Order By: Relevance
“…As for the tiresome driving tasks, the results showed a clear and tangible increase in the average response time than it was in the nonfatigue driving task, where the increase in response time increased gradually, with the highest average response time being recorded in the last quarter of an hour, where the average response time was 1.23 seconds. The results in this study are in agreement with the findings of the studies [11], [15], [24], where the reason for this increase is attributed to mental fatigue resulting from driving conditions represented by lack of sleep and examination time, which represents the second peak of sleep fatigue, as shown in Figure (6). The results of this study showed that when comparing the average cognitive time for fatigued and non-Fatigue driving tasks, there was a clear change in the response time for the participants.…”
Section: For All Participantssupporting
confidence: 93%
See 2 more Smart Citations
“…As for the tiresome driving tasks, the results showed a clear and tangible increase in the average response time than it was in the nonfatigue driving task, where the increase in response time increased gradually, with the highest average response time being recorded in the last quarter of an hour, where the average response time was 1.23 seconds. The results in this study are in agreement with the findings of the studies [11], [15], [24], where the reason for this increase is attributed to mental fatigue resulting from driving conditions represented by lack of sleep and examination time, which represents the second peak of sleep fatigue, as shown in Figure (6). The results of this study showed that when comparing the average cognitive time for fatigued and non-Fatigue driving tasks, there was a clear change in the response time for the participants.…”
Section: For All Participantssupporting
confidence: 93%
“…And [15], after testing 30 participants, showed a clear increase in cognitive time for drivers in tiring driving tasks compared to non-fatigue, as the increase was estimated at 0.31 milliseconds. In addition, [11] tested 30 participants in a driving simulator in fatigued driving tasks and alert driving tasks, the results showed a clear and tangible increase in the response time, as the increase was estimated (0.5) milliseconds. [16] also tested 22 participants with a driving simulator with multiple driving tasks, including fatigued and non-fatigue driving tasks.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies of sleep restriction suggest that cognitive deficits accumulate when adults attain less than 7 hr per night (Goel et al, 2009). Chronic sleep restriction, which is not uncommon in a military environment, can result in cognitive deficits equivalent to those observed after 24 hr of wakefulness (Van Dongen et al, 2003), and this level of sleep deprivation results in deleterious effects similar to drink‐drive limits (Fairclough & Graham, 1999; Lowrie & Brownlow, 2020). Further, emotional, behavioural and functional dysfunction have all been identified in a military context following poor sleep quality (Mantua et al, 2020; Mantua, Bessey, et al, 2021a).…”
Section: Discussionmentioning
confidence: 99%
“…It is unlikely there is one single explanation, but we have argued that the sedating effects of alcohol and drugs (as opposed to the intoxicating effects) are an understudied contributor of impaired driving crashes [ 18 – 20 ]. While drowsiness produces quantitative decrements in driving-related skills similar to alcohol and some drugs [ 21 ], we argue that falling asleep behind the wheel (for which drowsiness is a precursor) represents a qualitative change in crash risk. Crashes due to quantitative skill impairment require there being objects to track and avoid, things to drive around and react to, situations requiring decision making, etc.…”
Section: Discussionmentioning
confidence: 99%